TRAINING ON THE BLENDED LEARNING DESIGN AS A SUPPLEMENT TO A LEARNING APPROACH AT PRIMARY SCHOOLS - SUHARTONO SUHARTONO; JAMALUDIN JAMALUDIN; Sri SUMIYATI (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2019)
SD Negeri Purworejo is a primary school with adequate learning facility, such as computer laboratories, projectors, and internet connection. Although teachers, students, and parents have the access and the skills to use information technology, the school facility has not been optimally used. It is assumed that the application of such skills and the use of school facility will improve the learning process and the students’ learning outcomes. In this case, information technology is used to combine a face-to-face learning process and an online learning process, which is known as “blended learning”. The twenty-four teachers of SD Negeri Purworejo did not have prior experience with the blended learning process, although they have the potential to apply it in their class. The solution for this is to hold a workshop on Blended Learning. The materials of the workshop should include blended learning planning, blended learning practical implementation, and information on the supporting materials required in blended learning. The methods used in the workshop are lecture, practicum, and simulation. The outcomes are offline and online lesson plans.